Utilization of a Community-based Participatory Approach to Design and Implement a Peer-led Parenting Pilot Intervention to Influence Child Nutritional and Physical Activity Behaviors - Tabia Henry Akintobi, PhD, MPH; David Satcher; Victor Ede, MBBS; Glenda Wrenn, MD; Cassandra Bolar, PHD; Aneeqah Ferguson; Evonne Perdue; Martha Okafor; Kisha Holden; LeRoy Reese, PhD (Georgia Southern University, 2020)
Parents and primary child guardians within the household play critical roles in shaping their children's nutritional and physical activity behaviors, which are among the individual-level determinants of childhood obesity and other chronic conditions. There are well-established correlations between race, socioeconomic status and the risk for obesity calling for both contextually- and individual-centered interventions that are community-driven. The Using Quality Parenting (UQP) pilot intervention was a peer-led, parenting education intervention developed in collaboration with community residents in Atlanta, Georgia to influence child nutritional and physical activity behaviors in African American low socioeconomic status communities. A community-based participatory research (CBPR) framework was used to conduct a mixed-methods needs assessment designed to the UQP curriculum. The UQP program targeted parents of children ages 6-14. The overarching aim was to increase quality parenting and address community identified child obesity disparities and inequities in early and middle childhood. The topics pertaining to parenting to children's health/well-being addressed by the UQP included nutrition, physical activity, socio-emotional development, positive parenting, coping skills, child advocacy, and community development. Analyses were conducted using PSAW 18 statistical software. Descriptive statistics, including frequencies, means, standard deviations, and ranges for the individual survey items were conducted. A t-test was performed comparing pre- and post-program participation. A repeated measure analysis of variance was conducted on the items that demonstrated a significant t-test. The analytic sample was composed of 46 African American parents, with over 50% of the sample earning an annual household income of $25,000 or less. Participating parents reported significantly higher levels of water consumption for their children post-program in comparison to pre-test reports (p = .010). Additionally, based on t-test analyses, parents reported that their children consumed significantly higher levels of proteins, grains, fruits and vegetables at each meal, post-program (p=0.03). These findings highlight the potential efficacy of community-informed, parent-led interventions in improving health disparities and related outcomes for children.